The Effect of Cage Enrichment on Egg Weight, Hatchability and Hatch Weight of Padjadjaran Parent Stock Quail - Choirunnisa, Azkiya; Setiawan, Iwan; Sujana, Endang (Jurnal Produksi Ternak Terapan, 2025)
Parent stock quails require special attention in cage management to prevent stress that may affect their productivity. Therefore, this study was conducted to determine the effect of environmental enrichment in cages on egg weight, hatchability, and hatch weight of Padjadjaran parent stock quails. The research was carried out from 1 February-27 April 2025 at the Padjadjaran Quail Breeding Center, Faculty of Animal Husbandry, Padjadjaran University. The research subjects consisted of 100 Padjadjaran parent stock quails, including 80 black line females and 20 brown line males. The study was conducted experimentally using a completely randomized design (CRD) with four treatments: P1 (wire ram cage), P2 (wire ram cage with litter), P3 (wire ram cage equipped with nesting facilities and synthetic grass), and P4 (wire ram cage with litter equipped nesting facilities and synthetic grass). Each treatment was repeated five times, with each replicate consisting four females and one male. The results showed that the average egg weight 11.78 g, hatchability 74.14% and hatch weight 8.18 g. Environmental enrichment of cages using litter, nesting facilities and synthetic grass had no effect on egg weight, hatchability and hatch weight of Padjadjaran parent stock quails.